Determinants of Accounting Information System Performance at PT Perdana Adhi Lestari - Brilyan Mega Saputra; Sindy Astuti; Herzen Eduard Kumayas; Alexandra Amadea Christie; Luke Suciyati Amna (International Journal of Economics, Business and Innovation Research, 2024)
Tight competition in the era of globalization requires many companies to carry out their operational activities efficiently and effectively to maintain their existence. Accounting information systems will significantly help the effectiveness and efficiency of company performance. This research analyzes and tests aspects that influence the performance of accounting information systems, including user involvement, user capabilities, user training and education, and formalization of information system development. This research will see how influential these aspects are on the performance of accounting information systems in the researched topic. This study uses a saturated sampling technique method. The population in the study were all employees of the accounting department who use the IT system and the finance department at PT. Perdana Adhi Lestari, with 35 employees as respondents. Data processing using the SPSS application version 25. The findings of this research are that User Involvement, User Capabilities, User Training and Education, and Formalization of Information System Development have positive and significant effects on Accounting Information System Performance.